Friction-stir welding of high-strength aluminium alloys and a numerical simulation of the plunge stage - Perović, Milenko A. (Materiali in tehnologije, 2012)
This paper defines a set of welding parameters for the Friction-Stir Welding (FSW) of two forged panels of the alloy EN AW 7049A in a T652 temper and discusses the plunge stage of FSW using numerical modeling. This multi-component aluminum alloy is characterized by high strength, reduced plasticity and poor weldability. Observations of the macrostructure and microstructure clearly showed typical zones of a FSW joint and the appropriate grain sizes. The finest grains were observed within the nugget, while the coarsest grains are found to be in the HAZ. The ultimate tensile strength is 80.3 % of the parent material. A coupled thermo-mechanical model was developed to study the temperature fields and the plunge force of the alloy EN AW 7049A under different rotating speeds, (300, 400 and 500) r/min, during the FSW process of the plunge stage. A three-dimensional FE model has been developed in ABAQUS/Explicit using the arbitrary Lagrangian-Eulerian formulation, the Johnson-Cook material law and Coulombćs Law of Friction. Numerical results indicate that the maximum temperature in the FSW process canbe increased with an increase in the rotational speed, which can be used toreduce the plunge force.
Keywords: friction-stir welding; vrtilno torno varjenje; welding parameters; varilni parametri; metallography; metalografija; mechanical test; mehanski preizkusi; numerical simulation; numerična simulacija; plinge stage; faza taljenja; temperatura; temperature; force; sila